Association of Tear Cytokine Concentrations with Symptoms and Signs of Dry Eye Disease: Baseline Data from the Dry Eye Assessment and Management (DREAM) Study. (3rd April 2023) - Roy, Neeta S.; Wei, Yi; Ying, Gui-Shuang; Maguire, Maureen G.; Asbell, Penny A.
Abstract: Purpose: To describe tear concentrations of IL-1β, Il-6, IL-8, IL-10, IL-17A, IFNγ and TNFα in tears, collected by microcapillaries, and their correlation with symptoms and signs in subjects with dry eye disease (DED) in the DREAM Study. Methods: Cytokine levels of patients with moderate to severe DED were determined using a magnetic bead assay. Scores for Ocular Surface Disease Index, corneal and conjunctival staining, tear break-up time (TBUT), and Schirmer's test were obtained using standardized procedures. Associations of cytokines with each other and signs/symptoms were assessed with Spearman correlation coefficients (r). Results: Assay results from 131 patient samples from 10 sites with tear volumes ≥ 4 ul were analyzed. Cytokine concentrations did not correlate with each other in a generally acknowledged pro-inflammatory/anti-inflammatory pattern, such as proinflammatory IL-17A and IFNγ were not inversely correlated to anti-inflammatory cytokine IL-10, and cytokines did not correlate with DED symptoms. Lower corneal staining was correlated with higher concentrations of IL-17A (r= −0.24, p = 0.006), IL-10 (r= −0.25, p = 0.005) and IFNγ (r= −0.33, p = 0.0001). Higher concentrations of IFNγ were associated with lower conjunctival staining (r= −0.18, p = 0.03). Higher concentrations of IL-17A were associated with higher TBUT scores ( r = 0.19 p = 0.02). Conclusions: Cytokines IL-10, IL-17A and IFNγ were highly correlated with each other but weakly correlated with some DED signs. No key cytokines or definitive expression patterns were identified in this study of moderate to severe DED patients. Further studies addressing various biases, including methodological and sampling biases, and standardization of methodology for inter-laboratory consistency are needed to confirm and establish pathological and clinical relevance of tear cytokines in DED.